Heartwood and sapwood variation in Acacia melanoxylon R. Br. trees in Portugal - Knapic, Sofia (2006)
The development of heartwood and sapwood in blackwood ( Acacia melanoxylon R. Br.) was studied in a total of 20 trees with a 40-cm-diameter class sampled over four stands in northern Portugal at harvest for timber production. Stem discs with 5-cm thickness were taken at different height levels (stem base and 5, 15, 35, 50, 65, 75, 85 and 90 per cent of total height). Crosssectional area and heartwood area were measured by image analysis. Heartwood represented a substantial part of the trees and within the tree it attained on average 81 per cent of total height, and represented 69, 62, 58 and 44 per cent of the stem cross-sectional area, respectively, at 5, 35, 50 and 65 per cent of total tree height. The heartwood followed closely the stem wood profi le both axially and radially. Estimation of heartwood dimensions from external wood diameters (either over or under bark) was possible using a linear model, which had a very high correlation coeffi cient ( R 2 = 0.97). The sapwood radial width showed a very small variation within and between trees and maintained a constant value of 31 mm up to ∼ 65 per cent of tree height. No site infl uence was found for the heartwood development and the between-tree variation was small. The species and the sampled individuals in Portugal showed potential for the diversifi cation of forest production and increasing the industrial supply of a valuable timber hardwood